Analysis of the terms of usage of non-removable restorations fixed by different glass ionomer cements - Yanishen, I.; Sidorovа O.; Berezhna, O.; Saliya, L.; Bugaiev, V. (Journal of Education, Health and Sport, 2021)
Preservation and restoration of dental health of patients is achieved by early detection and treatment of diseases, finding ways of individual prevention, detection and elimination of risk factors for their development. The amount of materials significantly increased used to restore the integrity of teeth and dentition. Among them are dental materials for permanent fixation of indirect non-removable restorations. The material is used to fill the space between the inner surface of the artificial structure and the support element. This helps to mechanically fix the restoration in place to prevent its displacement during chewing. The correct choice of dental material for permanent fixation is an important decision and will determine the long-term success of permanent restorations. The aim of the study is to analyze the durability using non-removable structures of dentures mounted on different glass ionomer cements.